Titanium peroxide nanoparticles enhanced cytotoxic effects of X-ray irradiation against pancreatic cancer model through reactive oxygen species generation in vitro and in vivo. Issue 1 (December 2016) - Nakayama, Masao; Sasaki, Ryohei; Ogino, Chiaki; Tanaka, Tsutomu; Morita, Kenta; Umetsu, Mitsuo; Ohara, Satoshi; Tan, Zhenquan; Nishimura, Yuya; Akasaka, Hiroaki; Sato, Kazuyoshi; Numako, Chiya; et al.
Abstract Background Biological applications of nanoparticles are rapidly increasing, which introduces new possibilities to improve the efficacy of radiotherapy. Here, we synthesized titanium peroxide nanoparticles (TiOxNPs) and investigated their efficacy as novel agents that can potently enhance the effects of radiation in the treatment of pancreatic cancer. Methods TiOxNPs and polyacrylic acid-modified TiOxNPs (PAA-TiOxNPs) were synthesized from anatase-type titanium dioxide nanoparticles (TiO2 NPs). The size and morphology of the PAA-TiOxNPs was evaluated using transmission electron microscopy and dynamic light scattering. The crystalline structures of the TiO2 NPs and PAA-TiOxNPs with and without X-ray irradiation were analyzed using X-ray absorption. The ability of TiOxNPs and PAA-TiOxNPs to produce reactive oxygen species in response to X-ray irradiation was evaluated in a cell-free system and confirmed by flow cytometric analysis in vitro. DNA damage after X-ray exposure with or without PAA-TiOxNPs was assessed by immunohistochemical analysis of γ-H2AX foci formation in vitro and in vivo. Cytotoxicity was evaluated by a colony forming assay in vitro. Xenografts were prepared using human pancreatic cancer MIAPaCa-2 cells and used to evaluate the inhibition of tumor growth caused by X-ray exposure, PAA-TiOxNPs, and the combination of the two. Results The core structures of the PAA-TiOxNPs were found to be of the anatase type. The TiOxNPs and PAA-TiOxNPs showed a distinct ability to produce hydroxyl radicals in response to X-ray irradiation in a dose- and concentration-dependent manner, whereas the TiO2 NPs did not. At the highest concentration of TiOxNPs, the amount of hydroxyl radicals increased by >8.5-fold following treatment with 30 Gy of radiation. The absorption of PAA-TiOxNPs enhanced DNA damage and resulted in higher cytotoxicity in response to X-ray irradiation in vitro. The combination of the PAA-TiOxNPs and X-ray irradiation induced significantly stronger tumor growth inhibition compared to treatment with either PAA-TiOxNPs or X-ray alone (p  < 0.05). No apparent toxicity or weight loss was observed for 43 days after irradiation. Conclusions TiOxNPs are potential agents for enhancing the effects of radiation on pancreatic cancer and act via hydroxyl radical production; owing to this ability, they can be used for pancreatic cancer therapy in the future.